2018
DOI: 10.1111/jcmm.13581
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 sustains the metastatic phenotype of prostate cancer cells via EMT control

Abstract: Metastasis is the primary cause of death in prostate cancer (PCa) patients. Effective therapeutic intervention in metastatic PCa is undermined by our poor understanding of its molecular aetiology. Defining the mechanisms underlying PCa metastasis may lead to insights into how to decrease morbidity and mortality in this disease. Glyoxalase 1 (Glo1) is the detoxification enzyme of methylglyoxal (MG), a potent precursor of advanced glycation end products (AGEs). Hydroimidazolone (MG‐H1) and argpyrimidine (AP) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 120 publications
3
69
0
Order By: Relevance
“…28,29 Gene Silencing Glo1 silencing was performed as previously described. 23,27 Briefly, cells were transiently transfected with a pool of four siRNA oligonucleotides targeting Glo1 (ON-TARGET plus SMART pool siRNA) or with a pool of nontargeting siRNA oligonucleotides (siCtr) (ON-TARGET plus siCONTROL) to exclude off-target effects (all from Dharmacon RNA Technologies, Carlo Erba, Milan, Italy), using DharmaFECT 2 transfection reagent (Dharmacon RNA Technologies, Carlo Erba, Milan, Italy), according to the manufacturer's instructions and as previously described. 25,47 Knockdown of Glo1 was verified biochemically (protein and enzymatic activity) and at the molecular level (transcript) by Western blotting and spectrophotometric assay, or RT-qPCR, respectively.…”
Section: Apoptosis Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 Gene Silencing Glo1 silencing was performed as previously described. 23,27 Briefly, cells were transiently transfected with a pool of four siRNA oligonucleotides targeting Glo1 (ON-TARGET plus SMART pool siRNA) or with a pool of nontargeting siRNA oligonucleotides (siCtr) (ON-TARGET plus siCONTROL) to exclude off-target effects (all from Dharmacon RNA Technologies, Carlo Erba, Milan, Italy), using DharmaFECT 2 transfection reagent (Dharmacon RNA Technologies, Carlo Erba, Milan, Italy), according to the manufacturer's instructions and as previously described. 25,47 Knockdown of Glo1 was verified biochemically (protein and enzymatic activity) and at the molecular level (transcript) by Western blotting and spectrophotometric assay, or RT-qPCR, respectively.…”
Section: Apoptosis Detectionmentioning
confidence: 99%
“…25,47 Knockdown of Glo1 was verified biochemically (protein and enzymatic activity) and at the molecular level (transcript) by Western blotting and spectrophotometric assay, or RT-qPCR, respectively. 23 Mock transfection was performed to control for nonspecific effects of the transfection reagent. Because siCtr-or mock-treated and nontransfected cells were indistinguishable in the assays of biological phenomena examined here (data not shown), the observed changes were shown with respect only to siCtr-exposed cells.…”
Section: Apoptosis Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance can be formed through a variety of mechanisms, both intrinsic and extrinsic, but the details remain largely unknown. 5 Among various miRNAs, miR-129 has been shown to play a key role in tumourigenesis, tumour progression, chemotherapy resistance and cell proliferation. 4 Recently, studies have shown that miRNAs are frequently misregulated in many types of human cancers.…”
mentioning
confidence: 99%
“…For instance, some may act as potent oncogene promoting tumour growth and migration but demoting apoptosis, while others may act as tumour suppressor genes by targeting downstream genes to inhibit migration and invasion of tumour cells. 5 Among various miRNAs, miR-129 has been shown to play a key role in tumourigenesis, tumour progression, chemotherapy resistance and cell proliferation. 6 For instance, miR-129 was initially confirmed to be decreased in undifferentiated gastric cancer tissue, colorectal, gastric and liver cancer.…”
mentioning
confidence: 99%